L,L-diaminopimelate aminotransferase (DapL): a putative target for the development of narrow-spectrum antibacterial compounds - Triassi, Alexander J.; Wheatley, Matthew S.; Savka, Michael A.; Gan, Han Ming; Dobson, Renwick C. J.; Hudson, André O. (Frontiers in Microbiology, 2014)
Despite the urgent need for sustained development of novel antibacterial compounds to combat the drastic rise in antibiotic resistant and emerging bacterial infections, only a few clinically relevant antibacterial drugs have been recently developed. One of the bottlenecks impeding the development of novel antibacterial compounds is the identification of new enzymatic targets. The nutritionally essential amino acid anabolic pathways, for example lysine biosynthesis, provide an opportunity to explore the development of antibacterial compounds, since human genomes do not possess the genes necessary to synthesize these amino acids de novo. The diaminopimelate (DAP)/lysine (lys) anabolic pathways are attractive targets for antibacterial development since the penultimate lys precursor meso-DAP (m-DAP) is a cross-linking amino acid in the peptidoglycan (PG) cell wall of most Gram-negative bacteria and lys plays a similar role in the PG of most Gram-positive bacteria, in addition to its role as one of the 20 proteogenic amino acids. The L,L-diaminopimelate aminotransferase (DapL) pathway was recently identified as a novel variant of the DAP/lys anabolic pathways. The DapL pathway has been identified in the pathogenic bacteria belonging to the genus; Chlamydia, Leptospira and Treponema. The dapL gene has been identified in the genomes of 381 or approximately 13% of the 2,771 bacteria that have been sequenced, annotated and reposited in the NCBI database, as of May 23, 2014. The narrow distribution of the DapL pathway in the bacterial domain provides an opportunity for the development and or discovery of narrow spectrum antibacterial compounds.